Psicologia escolar e deficiência mental: um olhar bioecológico sobre a inclusão - Amazonas, Mariângela Mello Pereira (2008)
This research aimed to investigate issues related to scholar psychologists' professional practices and its relationship to the process of mental deficient person scholar inclusion. As a theoretical reference, it is adopted the Human Development Bioecological Theory, also having support on aspects of the critical perspective on Scholar Psychology. The study starts with a theoretical review on Scholar Psychology history in Brazil, the historical conceptions on mental deficiency in Brazil, some issues on the education of the deficient person, and on the scholar psychologist action related to the attendance of mental deficient person. Next, we presented the results of our research, developed within a qualitative approach to scientific investigation, involving the participation of seven scholar psychologists that work or have worked on mental deficient children in regular schools and/or in special schools in a mid size city in Minas Gerais state. Reflexive semi-structured individual interviews with the psychologists were carried out by means of a pre-established guide. The interviews were submitted to a category analyzes according to the Grounded Theory. By means of a bioecological view, the research was analyzed and discussed having in mind the scholar psychologist and the child bearing mental deficiency as parts of a complex society, structures through dynamic inter-relations within a socio-historical-cultural process. The research reached several conclusions, related to the interviewed professionals concepts and practices concerning the mental deficient person scholar insertion, remarkably that: first, there is still a considerable difficulty in making it clear the role of the psychologist within the scholar institution, both by the school s professionals and the psychologists themselves; second, it is possible to realize that the attendance performed had an individualized feature, marked by a lack of inter-relation between the actions done, restricted to given spaces and isolated in its width, affecting the possibility for an adequate ecological insertion of the student; third, the interviewed professionals practices confirm the integrationist and excluding position of the regular school, as they legitimate a psychological intervention driven by an emphasis on the student adaptation to the expectations of the educational official system, which is supported by an educational ideology based on a medical conception of the mental deficiency phenomenon.